REKONSTRUKSI ULANG LATAR BELAKANG PROFESI IBU SUSU (MURDHI’AT) DI MAKKAH MENJELANG KEDATANGAN ISLAM - Jati Pamungkas; Abdul Rosyid (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
This paper discusses the profession of wet nurse or murdhi'at in Mecca during the jahiliyah period, before Islam. This paper explains that there are several factors that caused the Quraysh Arabs to send their children to women called murdhi'at outside of Mecca. The factors described in this paper will provide a new understanding from the perspective of historical studies combined with the study of social change, especially after the Year of the Elephant and the period after it. This paper uses a qualitative method from the historical aspect by collecting literature that explains the murdhi'at or wet nurse in Mecca. The purpose of this study is to reveal the background of the existence of the wet nurse profession or murdhi'at in Mecca.